KOMPETENSI, KOMPENSASI DAN MOTIVASI PENGARUHNYA TERHADAP KINERJA TENAGA KESEHATAN (Studi Pada Perawat PNS Ruang Inap Rumah Sakit Umum Daerah dr. H. Moch Ansari Saleh Banjarmasin) - Eka Fakhrun Novianty; Basuki Basuki; Kurniaty Kurniaty (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2020)
The hospital was formed to serve consumers in the health sector. To achieve success, a strong foundation is needed, namely an organization that is able to strengthen and maximize the performance of its employees. The performance of health workers is the most important part in a hospital, because it can determine the progress or withdrawal of a hospital.This study aims to test and analyze the effect of competence, compensation and motivation on the performance of Health Workers at the Regional Public Hospital dr. H. Moch Ansari Saleh Banjarmasin with a sample of 50 Civil Servant Nurse Inpatient. The analysis uses multiple regression.The results of the study prove that partially the competence has a positive and significant effect on the performance of health workers (t count 3.044, α 0.004). Compensation has a positive but not significant effect (t count 0.498, α 0.621). Motivation has a positive and significant effect (t count 3.342, α 0.001). Simultaneously Competence, Compensation, and Motivation Improve the Performance of Health Workers at the Regional Public Hospital dr. H. Moch. Ansari Saleh Banjarmasin. Competence,   Compensation,   and  Motivation  affect  the  Performance  of   Health Workers at the Regional Public Hospital dr. H. Moch. Ansari Saleh Banjarmasin with an F count (8,711) > from an F table (2.80) and a significance value of 0,000 < 0.05